Effect of added ingredients on water status and physico-chemical properties of tomato sauce. (1st December 2017) - Diantom, Agoura; Curti, Elena; Carini, Eleonora; Vittadini, Elena
Highlights: Different ingredients were added to tomato sauce. Water status and physico-chemical properties of tomato sauce samples were studied. Added ingredients modulated physico-chemical properties at different time-space levels. Only 1 H NMR parameters were able to differentiate ingredients in tomato sauce. Abstract: Different ingredients (guar, xanthan, carboxy methyl cellulose, locust bean gums, potato fiber, milk, potato and soy proteins) were added to tomato sauce to investigate their effect on its physico-chemical properties. The products were characterized in terms of colour, rheological properties (Bostwick consistency, flow behavior and consistency coefficient), water status (water activity, moisture content) and molecular mobility by 1 H Nuclear Magnetic Resonance (NMR). Water activity was significantly decreased only by the addition of potato fiber. Xanthan, locust bean, guar and carboxy methyl cellulose significantly enhanced Bostwick consistency and consistency coefficient. Type of ingredient and concentration significantly affected 1 H NMR mobility indicators. Principal component analysis (PCA) indicated that only 1 H NMR mobility parameters were able to differentiate the effect of milk protein, xanthan and potato fiber on tomato sauce properties. The information collected in this work provides information to intelligently modulate tomato sauce attributes and tailor its properties for specific applications.